Surgical smoke: a matter of hygiene, toxicology, and occupational health - Kahramansoy, Nurettin (German Medical Science GMS Publishing House, 2024)
The use of devices for tissue dissection and hemostasis during surgery is almost unavoidable. Electrically powered devices such as electrocautery, ultrasonic and laser units produce surgical smoke containing more than a thousand different products of combustion. These include large amounts of carcinogenic, mutagenic and potentially teratogenic noxae. The smoke contains particles that range widely in size, even as sms 0.007 µm. Most of the particles (90%) in electrocautery smoke are ≤6.27 µm in size, but surgical masks cannot filter particles smaller than 5 µm. In this situation, 95% of the smoke particles which pass through the mask reach deep into the respiratory tract and frequently cause various symptoms, such as headache, dizziness, nausea, eye and respiratory tract irritation, weakness, and abdominal pain in the acute period. The smoke can transport bacteria and viruses that are mostly between 0.02 µm and 3 µm in size and there is a risk of contamination. Among these viruses, SARS-CoV-2, influenza virus, HIV, HPV, HBV must be considered. The smoke may also carry malignant cells. The long-term effects of the surgical smoke are always ignored, because causality can hardly be clarified in individual cases. The quantity of the smoke changes with the technique of the surgeon, the room ventilation system, the characteristics of the power device used, the energy level at which it is set, and the characteristics of the tissue processed. The surgical team is highly exposed to the the surgeon experiencing the highest exposure. However, the severif exposure differs according to certain factors, e.g., ventilation by laminar or turbulent mixed airflow or smoke evacuation system. In any cae surgical smoke must be removed from the operation area. The most effective method is to collect the smoke from the source through an aspiration system and to evacuate it outside. Awareness and legal regulations in terms of hygiene, toxicology, as well as occupational health and safety should increase.